Analysis of Lead Heavy Metal (Pb) Contamination on Matte Lipstick Preparations for Sale in Banda Aceh City Aceh Market - Rizki Andalia; Mulia Aria Suzanni; Rini Rini (Serambi Journal of Agricultural Technology, 2020)
Lipstick or lip dye is a cosmetic dose that serves to coloring, decorative the lips, as a moisturizing material and protect the lips from exposure the sun to provide optimum results. Lipstick should not contain chemicals such as lead (Pb) because the Pb is a heavy metal that is very dangerous when continuously used on the skin, because it will be absorbed into the blood and attack the body organ causing the onset of disease. According to BPOM that the lead rate on the lipstick does not exceed the permissible limit of 20 mg/kg or 20 ppm.This research aims to know the levels contained in the samples are 4 brands of matte lipstick that are sold in the Aceh market in Banda Aceh City with the method of atomic absorption spectrophotometry (AAS). The results showed that on the 4 brands of lipstick matte contain heavy metal lead (Pb) with a rate still qualified allowed by BPOM  is samples A, B, C, and D, respectively at 0.24 ppm; 0.10 ppm; 2.87 ppm and 1.32 ppm, so that the 4 brands of lipstick matte are still used.